Two cases with chloroquine and hydroxychloroquine maculopathy [Klorokin ve hidroksiklorokin makülopatili i̇ki olgu] - (:unkn) unknown (My University, 2011)
We described two cases of retinopathy due to antimalarial drugs and evaluated drug screening methods in antimalarial treatment. We reviewed our clinical records, fundus photographs, visual fields and the fluorescein angiographies of two patients from our retina referral department. The first case arose due to the misinterpretation of test results, despite the presence of adequate screening tests. The second case arose because of the inadequate information about the importance of screening tests.
Keywords: Chloroquine; Hydroxychloroquine; Retinal toxicity